2020
DOI: 10.3389/fcell.2020.00226
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of High Mobility Group Box Protein 1 in the Idiopathic Inflammatory Myopathies

Abstract: Introduction: High Mobility Group Box Protein 1 (HMGB1) is a DNA-binding protein that exerts inflammatory or pro-repair effects upon translocation from the nucleus. We postulate aberrant HMGB1 expression in immune-mediated necrotising myopathy (IMNM). Methods: Herein, we compare HMGB1 expression (serological and sarcoplasmic) in patients with IMNM with that of other myositis subtypes using immunohistochemistry and ELISA. Results: IMNM (n = 62) and inclusion body myositis (IBM, n = 14) patients had increased sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Additional in vitro studies have demonstrated that HMGB1 can accelerate muscle fatigue and induce major histocompatibility complex class I expression in muscle fibers by interacting with its receptor, Toll‐like receptor 4 (34). More recently, Day et al showed that sarcoplasmic HMGB1 expression correlated with muscle weakness and histologic myonecrosis, inflammation, regeneration, and autophagy in patients with IIM (35). In the present study, we found similar patterns of HMGB1 expression in the muscle tissue of patients with IIM.…”
Section: Discussionmentioning
confidence: 99%
“…Additional in vitro studies have demonstrated that HMGB1 can accelerate muscle fatigue and induce major histocompatibility complex class I expression in muscle fibers by interacting with its receptor, Toll‐like receptor 4 (34). More recently, Day et al showed that sarcoplasmic HMGB1 expression correlated with muscle weakness and histologic myonecrosis, inflammation, regeneration, and autophagy in patients with IIM (35). In the present study, we found similar patterns of HMGB1 expression in the muscle tissue of patients with IIM.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that autoimmune and inflammation response, to a great extent, contribute to the pathogenesis of IIM. Current research for the pathophysiology of IIM has mainly focused on immune and inflammatory response, such as autoantibodies ( Benveniste et al, 2016 ; Arouche-Delaperche et al, 2017 ; Darnoiseaux et al, 2019 ), complement ( Allenbach, Arouche-Delaperche et al, 2018 ; Bergua et al, 2019 ), cytokines ( Day et al, 2020 ), inflammatory cells ( Preuße et al, 2012 ; Rinnenthal et al, 2014 ; Knauss et al, 2019 ; Jiang et al, 2020 ; Seto et al, 2020 ), interferon-signature ( Greenberg et al, 2005 ; Gallay et al, 2019 ), and the upregulation of major histocompatibility complex—class I on myofibers ( Bhattarai et al, 2016 ; Wang et al, 2018 ). Although a previous study revealed evidence for activation of the ER stress response in polymyositis and DM ( Nagaraju et al, 2005 ; Alger et al, 2011 ), the functional role of ER stress was still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, infiltration of lymphocytes expressing Bcl-2 and betachemokine receptor 4 (CCR4) (both negatively affected by statins) seemed to be a marker of anti-HMGCR+ IMNM (29). The High Mobility Group Box Protein 1 (HMGB1, a DNA-binding acting as a damage signal and pro-inflammatory mediator) was also overexpressed in IIMs muscle samples and serum, especially in IMNM (30). Moreover, Day et al (31) demonstrated that IMNM samples from different patients may display different degree of necrosis and that the amount of myofibre complement deposition was closely associated with clinical severity.…”
Section: Review Idiopathic Inflammatory Myopathies: One Year In Revie...mentioning
confidence: 99%